A Re-Appraisal of the Role of Blood Coagulation and Platelets in the Generalized Shwartzman Phenomenon - Levin, J; Beck, E (Thrombosis and Haemostasis, 1966)
The role of intravascular coagulation in the production of the generalized Shwartzman phenomenon has been evaluated. The administration of endotoxin to animals prepared with Thorotrast results in activation of the coagulation mechanism with the resultant deposition of fibrinoid material in the renal glomeruli. Anticoagulation prevents alterations in the state of the coagulation system and inhibits development of the renal lesions. Platelets are not primarily involved. Platelet antiserum produces similar lesions in animals prepared with Thorotrast, but appears to do so in a manner which does not significantly involve intravascular coagulation.The production of adrenal cortical hemorrhage, comparable to that seen in the Waterhouse-Friderichsen syndrome, following the administration of endotoxin to animals that had previously received ACTH does not require intravascular coagulation and may not be a manifestation of the generalized Shwartzman phenomenon.